Tunable coverage of immobilized biomolecules for biofunctional interface design1. (11th September 2015) - Wu, Jyun-Ting; Sun, Ting-Pi; Huang, Chao-Wei; Su, Chiao-Tzu; Wu, Chih-Yu; Yeh, Shu-Yun; Yang, Deng-Kai; Chen, Lin-Chi; Ding, Shih-Torng; Chen, Hsien-Yeh
<x xml:space="preserve">Abstract</x> Tunable biological responses can be controlled by the modifications of the density of the underlying chemical motifs and the density of the biomolecules immobilized.